PENGARUH LATIHAN SIDE (LATERAL) SHOULDER RAISE TERHADAP KEKUATAN OTOT LENGAN DAN BAHU PADA SAAT MELAKUKAN BATTING PADA TIM SOFTBALL PUTRA LASKAR RIAU - Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract, The purpose of this research is want to know is there effect of Side (Lateral) shoulder raise exercise toward strength of arm and shoulder when batting of Laskar Riau man softball club, so when a player do batting in softball, a ball hit hard into the outfield.Type of this research is exsperimental, The population in this research was the athletes of Laskar Riau Softball Man who actively doing exercise, the total was 10 athletes. Sampling technique used in this research was total sampling. Total sampling is all population are used as sample (Sugiono, 2008 : 124). Total sample of this research is 10 athletes of Laskar Riau Man Softball Club. Data technique used was surfeited, it is determination of the sample. The instrument was used in this research was Expanding Dynamometer, which is aimed to measure the strength of aim and shoulder muscles. After that, the data was analyzed by using statistic to examme the normality with liliefors test on the significant level 0,05α. The submitted hypothesis was there is the effect of Side (Lateral) shoulder raise exercise toward strength of arm and shoulder when batting of Laskar Riau man softball club Based on the data analyzed, t test shower t count was 13,93 and t tabel 1,833, it means that t count > t tabel. Based on the statistic data analyzed, the average of preetest was 23,9 and the average of posttest was 27,8, it shows that the data was normal. In conclution, there was the effect of Side (Lateral) shoulder raise exercise toward strength of arm and shoulder when batting of Laskar Riau man softball clubKey Point : Side (Lateral) Shoulder Raise, Strength of arm and shoulder muscles